THEORETICAL FOUNDATIONS AND SPECIFIC FEATURES OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In the reliable functioning of market principles, the businessman is primarily interested in the introduction of significant innovations. For the development of these innovations, large, complex centralized economic systems do not provide enough material and moral incentives of private property. The importance of economic problems in realizing the reuse of small business development is increasing, with its significant advantage in terms of cost and speed of use of new ideas over large bureaucratic associations. So, without consumer signals coming from the rapid expansion of a strong middle class with significant purchasing power as the main direction of modern economic growth, the effective solution of modern economic problems becomes impossible. Consequently, the perpetuation of the successes achieved earlier by the economy becomes impossible.